The wall : a novel - Lanchester, John (W.W. Norton & Company, 2019)
"The best-selling author of The Debt to Pleasure and Capital returns with a chilling fable for our time. Ravaged by the Change, an island nation in a time very like our own has built the Wall--an enormous concrete barrier around its entire border. Joseph Kavanagh, a new Defender, has one task: to protect his section of the Wall from the Others, the desperate souls who are trapped amid the rising seas outside and attack constantly. Failure will result in death or a fate perhaps worse: being put to sea and made an Other himself. Beset by cold, loneliness, and fear, Kavanagh tries to fulfill his duties to his demanding Captain and Sergeant, even as he grows closer to his fellow Defenders. And then the Others attack. . . . Acclaimed British novelist John Lanchester, "a writer of rare intelligence" (Los Angeles Times), delivers a taut dystopian novel that blends the most compelling issues of our time--rising waters, rising fear, rising political division--into a suspenseful story of love, trust, and survival"--